2011
DOI: 10.1111/j.1365-2265.2010.03910.x
|View full text |Cite
|
Sign up to set email alerts
|

Trimester- and method-specific reference intervals for thyroid tests in pregnant Chinese women: methodology, euthyroid definition and iodine status can influence the setting of reference intervals

Abstract: The trimester- and method-based reference intervals for thyroid tests during pregnancy are clinically appropriate. Some variables should be controlled when establishing reference intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
57
6
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(72 citation statements)
references
References 33 publications
7
57
6
2
Order By: Relevance
“…Two studies from China [18,19] and 1 study from India [20], for example, demonstrated a significantly higher TSH reference range for each trimester; in particular, the study by Li et al [19] showed that the Chinese population displays 0.12-5.08 mU/l as first trimester reference range; as a consequence, using the suggested 0.1-2.5 mU/l as reference range, about 28% of the pregnant patients in China would suffer from hypothyroidism, versus 4% when using an ethnically specific reference range [6,21,22,23]. Further data derived from the 3,944 women participating in the Generation R study demonstrated that a comparison of disease prevalence between a population-based versus an ethnicity-specific reference range changed the diagnosis for 18% of women who were initially diagnosed as having abnormal thyroid function test results [24].…”
Section: Diagnosis Of Sch In Pregnancymentioning
confidence: 99%
“…Two studies from China [18,19] and 1 study from India [20], for example, demonstrated a significantly higher TSH reference range for each trimester; in particular, the study by Li et al [19] showed that the Chinese population displays 0.12-5.08 mU/l as first trimester reference range; as a consequence, using the suggested 0.1-2.5 mU/l as reference range, about 28% of the pregnant patients in China would suffer from hypothyroidism, versus 4% when using an ethnically specific reference range [6,21,22,23]. Further data derived from the 3,944 women participating in the Generation R study demonstrated that a comparison of disease prevalence between a population-based versus an ethnicity-specific reference range changed the diagnosis for 18% of women who were initially diagnosed as having abnormal thyroid function test results [24].…”
Section: Diagnosis Of Sch In Pregnancymentioning
confidence: 99%
“…Due to a variety of physiological and hormonal changes in pregnancy, women with hypothyroidism have increased levothyroxine needs of 30-50% from as early as five weeks gestation (11)(12)(13). Additionally, laboratory reference ranges are not specific for pregnancy, and although there are published trimester-specific reference ranges for thyroid function tests, these are not universally agreed upon and not reported by laboratories (14)(15)(16)(17). The mother's free T4 of 0.8 ng/dL at 15 weeks would be considered <2.5% of the second trimester population according to one study (17), whereas the FaSTER trial (16) would classify 0.77 ng/dL at the 5th percentile in the second trimester.…”
Section: Vertical Transmission Of Hypopituitarismdiscussionmentioning
confidence: 99%
“…Additionally, laboratory reference ranges are not specific for pregnancy, and although there are published trimester-specific reference ranges for thyroid function tests, these are not universally agreed upon and not reported by laboratories (14)(15)(16)(17). The mother's free T4 of 0.8 ng/dL at 15 weeks would be considered <2.5% of the second trimester population according to one study (17), whereas the FaSTER trial (16) would classify 0.77 ng/dL at the 5th percentile in the second trimester. It should be noted that the index patient's mother's laboratory result was considered within normal limits based on the reported reference range of 0.61-1.76 ng/dL.…”
Section: Vertical Transmission Of Hypopituitarismdiscussionmentioning
confidence: 99%
“…Hay que considerar que en las publicaciones realizadas hasta ahora existe una variabilidad importante en los niveles de TSH para poder definir normalidad en las gestantes. Especialmente variable es el corte superior de TSH, el que podría estar influido por múltiples factores como: la etnia de origen, la edad media de las gestantes, diferentes métodos de análisis, el estatus de iodo, método de cálculo y las diversas consideraciones para la selección de pacientes "sanas" 12 . En nuestros datos, al excluir a la población con TPO positivo, obtuvimos un punto de corte de TSH en 5,4, muy superior al propuesto en las guías internacionales y sólo semejante al encontrado en una población en India 13 .…”
Section: Discussionunclassified